GOVERNANCE OF THE INTEGRATED HAJJ COMPUTERIZATION SYSTEM (SISKOHAT) IN PROMOTING TRANSPARENCY FOR HAJJ PILGRIMS IN ACCORDANCE WITH LAW NO. 14 OF 2025 IN KUDUS REGENCY - Zanatul Khoiriyah; Mustofa Hilmi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The ratification of Law Number 14 of 2025 requires Hajj organizers to implement the principle of transparency. However, implementation at the Kudus Regency PLHUT Office, SISKOHAT, still faces challenges in providing information openly to the public. The purpose of this study is to analyze in depth the governance of SISKOHAT in realizing transparency for Hajj pilgrims based on Law Number 14 of 2025 at the Kudus Regency PLHUT. This research method uses a descriptive-analytical qualitative research method. Data collection was carried out through in-depth interviews with relevant authorities as well as direct observation and documentation studies. The results of the study indicate that the governance of the Integrated Hajj Computerized System (SISKOHAT) is not yet transparent in accordance with Law Number 14 of 2025. This is due to the absence of a mechanism for real-time publication of SISKOHAT data through social media platforms and limited human resources (HR). These conditions limit pilgrims' access to departure status.